Redefining anaemia management in CKD: comparative insights on desidustat, roxadustat, and molidustat as oral HIF-PH inhibitors - Kaandeeban Mohanraj; Cheryl Singla; Vidhya Mohanraj; Vishnuvardan Venkatramanan (Clinical Medicine)
Introduction: Anaemia affects over 50% of advanced chronic kidney disease (CKD) patients, increasing cardiovascular mortality. Traditional erythropoiesis-stimulating agents (ESAs) require injections and carry risks, such as hypertension and thromboembolism. Hypoxia-inducible factor prolyl hydroxylase inhibitors (HIF-PHIs), including desidustat, roxadustat, and molidustat, offer oral alternatives by stabilising HIF-α mimicking hypoxia to enhance erythropoietin production and improve iron metabolism (Fig 1).1,2The objective of this study iwass to evaluate the efficacy, safety and cost-effectiveness of three HIF-PHIs compared with traditional ESAs in CKD-related anaemia management. Materials and Methods: A thorough review of clinical trials, meta-analyses and guidelines on the three HIF-PHIs were conducted. Key outcomes included haemoglobin (Hb) response rates, cardiovascular safety (MACE incidence), iron metabolism markers (hepcidin/ferritin), and 5-year treatment costs. Results and Discussion: Efficacy° Desidustat: non-inferior to ESAs in dialysis-dependent patients (59.22% Hb response vs 48.37%, p=0.0382) maintaining Hb of 10–12 g/dL and non-dialysis patients (77.78%, +1.95 g/dL vs darbepoetin alfa, +1.83 g/dL, p=0.0181) (Fig 2);° Roxadustat: maintained Hb levels of 10–12 g/dL in 78% of non-dialysis patients; non-inferior to darbepoetin alfa;° Molidustat: showed comparable efficacy to ESAs in ESA-treated patients (+0.36 g/dL vs +0.26 g/dL for darbepoetin alfa) but was less effective in ESA-naive patients (+1.44 g/dL vs +1.70 g/dL).SafetyHIF-PHIs showed similar cardiovascular safety to ESAs (MACE RR 0.99–1.08) with reduced hypertension incidence (-11%, p=0.03). Improved iron metabolism reduced intravenous iron needs (hepcidin -19 ng/mL; ferritin -16.8 ng/mL) (Fig 2).Cost-effectiveness (over 5 years)° Desidustat (100 mg three times a week): savings of £27,300–£35,880 compared with epoetin (£4,680–£6,240 vs £33,540–£40,560) (Fig 2);° Roxadustat (70–100 mg three times a week): savings of £18,720–£43,940 compared with darbepoetin (£13,260–£38,480 vs £57,200);° Molidustat (25–50 mg daily): savings of £30,420–£38,480 compared with epoetin (£2,080–£3,120 vs £33,540–£40,560).3–10 Conclusion: HIF-PH inhibitors offer a transformative approach to CKD anaemia management with oral convenience, improved iron utilisation, cardiovascular safety and significant cost savings over ESAs. However, long-term risks, such as vascular calcification and off-target HIF effects, require further study through phase IV trials (eg, DREAM-CKD). Clinicians should tailor treatment based on dialysis status and iron bioavailability for optimal outcomes.